Aspirations of People With Intellectual Disabilities Living in a Care Organization. (July 2022) - Benoot, Toon; Roose, Rudi; Dursin, Wouter; Verschuere, Bram; McKenzie, Judith
Summary: This article presents the results of a research project involving 10 people with intellectual disabilities concerning their idea of "a good life" in a residential care setting, within a context of personal budgets. We introduce the capability approach as a framework for focusing on the opportunities personal budgets offer for people with intellectual disabilities. We make use of qualitative interviews following a photovoice project in which people with intellectual disabilities documented their lives in order to research what they deem valuable and aspire to. Findings: In the analysis section, we present the elements which the participants identified as limiting and enhancing for imagining their future. From their stories, we learn that their aspirations are nourished by the encounters and social bonds that they engage in within a residential care context. The results make clear that the use of money offers opportunities to elaborate on what is already known and enables the realization of aspirations, while interactions with significant others more often than not encourage participants to explore and try out changes and thus further develop people's set of aspirations. Applications: In drawing the discussion to a close, we explore the implications these stories might have for understanding the role of aspirations in the practice of care and support for people with intellectual disabilities. The findings encourage us to think about a relational pedagogy and to address this in the practices of personal budgets.